Guide to Effective Grant Writing - Yang, Otto O. author. aut Link
XIV, 90 p.
Keywords: Getting funding from the NIH for research is one of the most important skills required of all academic researchers, and here, Otto O. Yang offers a fully updated second edition to his straightforward, common-sense Guide to Effective Grant Writing. Yang shares his perspectives from both ends: as a pioneering researcher applying for funding as well as an NIH scientific consultant reviewing grants. He provides the reader with a step-by-step account on how to write a successful grant application, while highlighting common errors. This definitive guide to the NIH review process is a must for any pioneering researcher. From the foreword: The bane of academic existence is grant writing, now more than ever given new economic realities that change an already challenging landscape. Yet without grants most of us would not be able to continue to ply our trade. With this enormous importance of grants, it is surprising that we are so well trained to do research, with so little attention given to grant writing, which is the lifeblood of academic research. Help became available with the first publication of this inspired book from Otto Yang MD, and now in its second edition it becomes even more invaluable. The book will be of great help to anyone writing a grant, even those of us who are more seasoned grant writers. The new edition is organized in similar fashion to the newly modified official NIH grant, readily helping the reader to navigate an entirely new terrain. Moreover, it outlines in very readable fashion specific suggestions for convincing study sections that the ideas being presented are worthy of funding, turning the reviewer into an advocate for the project being proposed. It also points out common errors that make reviewers lose enthusiasm even when the experiments are highly worthy of funding. Frequent use of examples makes the points very clear, and the clear style makes the book an enjoyableread. - Bruce D. Walker, Professor of Medicine and Director of the Partner’s AIDS Research Center at Harvard Medical School; Boston Massachusetts Former Chairman of an NIAID/NIH study section.